Silicon and gadolinium co-doped hydroxyapatite/PLGA scaffolds with osteoinductive and MRI dual functions - Xie, Shaodong; Guo, Min; Zeng, Deming; Luo, Hanwen; Zhong, Ping; Deng, Zixuan; Wang, Yu; Xu, Zhiqiang; Zhang, Peibiao (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: An ideal bone repair scaffold should have dual functions of osteoinductive ability and in vivo imaging. In this study, the simultaneous substitution of silicon (Si) and gadolinium (Gd) in hydroxyapatite (HA) as potential multifunctional bone graft materials has been successfully developed. Methods: A series of HA nanoparticles (HA NPs) doped with different proportions of Si and Gd were prepared. The chemical structure and phase composition of the materials were analyzed using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). The microstructure, magnetic properties, surface potential, and cytotoxicity of the materials were also analyzed. The magnetic resonance imaging (MRI) effect of Gd&Si-HA/poly(lactic-co-glycolic acid) (Gd&Si-HA/PLGA) composite materials was evaluated. Osteogenic-related gene expression, alkaline phosphatase (ALP) level, and mineralization capacity of MC3T3-E1 cultured on Gd&Si-HA/PLGA composite materials were also detected. Results and Discussion: The 1.5Gd&Si-HA@PLGA group showed good ability to promote osteogenic differentiation of cells. The MRI effect of the 1.5Gd&Si-HA@PLGA scaffold was observable. This HA material containing Si and Gd co-doping has a broad application prospect in the field of bone tissue engineering owing to its ability to enhance osteoinductive property and improve MRI effect.